Carbon Taxes: Their Macroeconomic Effects and Prospects for Global Adoption. A Survey of the Literature - Cuervo, Javier; Ved P., Gandhi (Desarrollo y Sociedad, 1999)
The carbon tax is a major instrument for curbing greenhouse gas emissions that cause global warning. Y et its adoption has been limited because of concerns over its effects on economic growth, income distribution, and international competitiveness. The paper shows that policymakers can minimize the effects of the tax on economic growth through an efficient recycling of tax revenues and on equity through the adoption of appropriate mitigating or compensating measures. To eliminate the worry about the loss of competitiveness, the paper suggests and international agreement on a coordinated adoption of the tax.